MEASURES AND RESULTS OF IMPROVING THE MATERIAL AND TECHNICAL BASE OF GENERAL EDUCATION INSTITUTIONS IN KASHKADARYA REGION (Scientific journal of the Fergana State University, 2023)
In the following article, during the years of independence, measures and results of improving the material and technical base of general education institutions in Kashkadarya region are analyzed. Great number of tasks have been carried out to completely renew the educational process in terms of quality and methodology, building new schools, complete reconstruction and provide them with modern educational and laboratory equipment.